Electrically conductive high-performance thermoplastic filaments for fused filament fabrication - Kaynan, Ozge; Yildiz, Alptekin; Bozkurt, Yunus Emre; Ozden Yenigun, Elif; Cebeci, Hulya (Elsevier BV, 2020)
Conductive polyetherimide (PEI)-based filaments can fill the gap between the design and manufacturing of functional and structural components through additive manufacturing. This study systematically describes the fabrication of carbon nanotube (CNTs)-reinforced PEI filaments, complemented by a custom-built extrusion process facilitating low weight fraction of nanomaterials. Neat PEI and CNTs/PEI filaments at different CNTs fractions ranging from 0.1 to 7 wt. % were fabricated. Supported by morphology analysis, the rheological percolation was found to be higher (0.25 wt. % CNTs/PEI) than electrical percolation (0.1 wt. % CNTs/PEI) since the system reached an electrical percolation within the formation of a continuous conductive path at lower CNTs loadings. With the 7 wt. % CNTs loading, the highest electrical conductivity of CNTs/PEI filaments was reported as 2.57 × 10−1 S/cm. A 55% enhancement in tensile modulus was achieved when 5 wt. % CNTs were introduced, but in a trade-off in elongation at break ca. 65%.
Keywords: H400 Aerospace Engineering